Investigating the effects of wrestling gear in flatfoot deformity of wrestlers - Acak, M.; Korkmaz, M. F.; Taskiran, C.; Demirkan, E. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2020)
Purpose: In this study, our aim was to determine the effects of wrestling shoes, wrestling mats and wrestling styles on postural deformation of the foot and to elaborate its possible causes. Material: Study group comprised of 158 athletes (109 males, 59 females) from 26 different countries who participated in the 12th World University Wrestling Championship. Of the athletes, 102 (59 females, 43 males) performed in freestyle and 56 performed in Greco-Roman style. The age range of the athletes was 19 to 31 years and they have done wrestling for 3 to 18 years. Were evaluated to determine the relationship between flatfoot deformity and gender, age, wrestling style and years in the sport. Footprint parameters were used to determine and evaluate the overall structure of the foot. The Staheli and the Chippaux-Smirak indexes were used in the study. Statistical analyses were performed using the SPSS v.21.0 software, with the significance level set at á=0.05. Results: No significant relationship was found either between the gender of the wrestlers or their age and their pes planus state. A significant relationship was detected between the wrestling style performed and the wrestlers` pes planus state, and between the years in the sport and their pes planus state. Conclusions: The fact that wrestlers wear the wrestling shoes for a long time can be a cause of pes planus. The center of mass of freestyle wrestlers shifts during continuous feet movement, and the surface of their soles extends the contact surface on the mat to maintain balance. This situation can also lead to a higher prevalence of pes planus in wrestlers. In addition, the wrestling shoes wrap around the Achilles tendon and thus the stretching of this tendon is restricted. Such restriction strengthens the opinion that freestyle wrestlers experience pes planus more.